Reorganization and educational reform in Jujuy (Argentina) during Peronism. The Common and Special Education Law (1946-1952) - Jerez, Marcelo (2018)
This study analyzes the transformations in the educational field that occurred during the first Peronist government in Jujuy (Argentina). We focus particularly on the reorganization and reform of the education system that followed the enactment of the Common and Special Education Law 1946. In this task we focus mainly on primary education in the district, as well as highlighting the role of the then Minister of Education in Jujuy: Shukri José.